Chemical Derivatization and Characterization of Novel Antitrypanosomals for African Trypanosomiasis - Aboagye Kwarteng Dofuor; Temitayo Samson Ademolue; Cynthia Mmalebna Amisigo; Kwaku Kyeremeh; Theresa Manful Gwira (Molecules, 2021)
The search for novel antitrypanosomals and the investigation into their mode of action remain crucial due to the toxicity and resistance of commercially available antitrypanosomal drugs. In this study, two novel antitrypanosomals, tortodofuordioxamide (compound 2) and tortodofuorpyramide (compound 3), were chemically derived from the natural N-alkylamide tortozanthoxylamide (compound 1) through structural modification. The chemical structures of these compounds were confirmed through spectrometric and spectroscopic analysis, and their in vitro efficacy and possible mechanisms of action were, subsequently, investigated in Trypanosoma brucei (T. brucei), one of the causative species of African trypanosomiasis (AT). The novel compounds 2 and 3 displayed significant antitrypanosomal potencies in terms of half-maximal effective concentrations (EC50) and selectivity indices (SI) (compound 1, EC50 = 7.3 μM, SI = 29.5; compound 2, EC50 = 3.2 μM, SI = 91.3; compound 3, EC50 = 4.5 μM, SI = 69.9). Microscopic analysis indicated that at the EC50 values, the compounds resulted in the coiling and clumping of parasite subpopulations without significantly affecting the normal ratio of nuclei to kinetoplasts. In contrast to the animal antitrypanosomal drug diminazene, compounds 1, 2 and 3 exhibited antioxidant absorbance properties comparable to the standard antioxidant Trolox (Trolox, 0.11 A; diminazene, 0.50 A; compound 1, 0.10 A; compound 2, 0.09 A; compound 3, 0.11 A). The analysis of growth kinetics suggested that the compounds exhibited a relatively gradual but consistent growth inhibition of T. brucei at different concentrations. The results suggest that further pharmacological optimization of compounds 2 and 3 may facilitate their development into novel AT chemotherapy.